Optimisation, immobilisation and application of alkaline protease produced by bacterial isolates from Tithal beach of valsad - R.B. MISTRY; P.C. SURVE; H.K. PANCHAL; R.G. DESAI (International Journal of Pharma and Bio Sciences, 2017)
Marine ecosystem is the least explored ecosystem of the earth which contains microbes capable of producing different compounds. Fourteen protease producing bacteria were isolated from marine water samples of Tithal beach, Valsad. All fourteen isolates were screened for their proteolytic activity. On the basis of results, two best protease producing isolates were further studied. The optimization for various parameters was performed. Isolate C-3 gave optimum protease activity at 24 hours time period, pH-8, at 37°C temperature, sucrose as carbon source, urea as nitrogen source, 0.5% salt concentration, whereas isolate C-14 showed optimum activity at 24 hours time period, pH-8, 37°C temperature, starch as carbon source, peptone as nitrogen source, 1% salt concentration. Partial ammonium sulphate purification was obtained best at 60% and 80% saturation for C-3 and C-14 respectively. 32% and 52.7% protease was entrapped in sodium alginate beads respectively from C-3 and C-14. Overall C-14 was found to be the best protease producer.